GROWTH AND SURVIVAL OF SEEDLINGS AND SAPLINGS IN THE LOGGED - OVER FOREST, KINTAP, SOUTH KALIMANTAN - Jafarsidik, Yusuf S. (Indonesian Journal of Forestry Research, 2004)
A study on demography, Â growth Â and survival ofÂ  seedlings and saplings was conducted Â in the Hutan Kintap Â concenssion,Â  Â South Kalimantan,Â  Â Indonesia. The aim of Â the study Â was to monitor Â pattern Â of growth of seedlings and saplings among different types of logged - Â over forest, including the newly Â logged Â - Â forest, older Â logged Â - Â over forestsÂ  Â (treated and untreated),Â  Â and un-logged-forestÂ Â  Â patches.Â  Â TheÂ  study began in 1991, and nineteen Â of Â 0.25 Â ha plotsÂ  Â were set up in a total Â of Â six blocks Â designatedÂ Â  as consecutively Â A, B, C, D, E and F. Â Block A was a newly loggedÂ  Â forest and had five plots, Â and Block Â B - Â D were in forest whichÂ  had been logged Â in 1979. Â Block B (five plots) had received no silviculturalÂ  Â treatment, Â while Block Â C (five plots) and Â D (one plot)Â Â  hadÂ  beenÂ  lightlyÂ  Â thinned Â after Â felling and Â further Â Block C received Â a further Â thinning treatmentÂ  Â Block Â E (one plot) Â had been Â heavilyÂ  Â thinned, Â and Block F (2 plots)Â  Â was an un-loggedÂ  Â control. TheÂ  densityÂ  of Â seedling Â varied within Â the study sites, and averaged Â from Â 47,000 ha" Â to 121,000Â  Â haÂ·1â¢Â  Â The mean height increment Â of Â seedlings varied among block ranging from 2.9 Â cm year Â to 10.5 Â cm year". Â Block A had the highest general Â mean Â increment Â of Â 10.5 Â cm year",Â  Â followed Â in decreasing Â order Â by Block C of 5.4 and Block F, 4.5 Â cm year". Â Growth Â of Â seedling in Block Â B was low, even lower Â than Â the growth Â in the un-loggedÂ  Â Block F. TheÂ  differenceÂ  of the increment among Block A, B, C and F however was not significant. The liberation treatment Â in Block C significantlyÂ  Â resulted in a higher (p<0.01) Â increment Â (5.4 cm year") than that in Â the untreated Â Block Â B (2.9 cm year"). Â Seedling Â mortality ranged from 16 to 37 % year", and declined with Â heightÂ  Â class. The Â mortality Â of Â seedlings Â mightÂ  be related Â among Â other Â factors Â to theÂ  humidity Â and density Â of Â seedlings per-unit Â area. TheÂ  density Â of Â sapling ranged Â from 6,800 ha" to 7,700 Â ha" and they had diameter Â growth Â of Â 0.8 mmÂ  year" to Â 2.2 Â mm year", Â and heightÂ  Â growth Â of Â 12.6 Â cm year" to 21.8 Â cm year"1. The Â difference Â in the Â diameter Â incrementÂ  Â among Â block Â r, B, Â C and Â F wasÂ  not Â significant.Â Â Â  The Â average sapling height increment Â varied (but not significantly so) among Block, Â ranging from 12.6 Â cm year" in Block A to 21.8 Â cm year" in Block C. Mortality Â of Â sapling was relativelyÂ  Â low Â in all block. Â Higher Â mortality Â in the un-loggedÂ  Â forest Â Block Â I and Â in the untreated Â Block B might Â due to Â the low Â degree Â of Â canopyÂ  Â opening.